A construção de instrumentos avaliativos para compreensão do processo de aquisição da língua materna em crianças do 1º Ano de Ensino Fundamental - Helmer, Ester Almeida (Universidade Federal de São Carlos, 2009)
The present work has as objective socialize the discussions that resulted in the present master dissertation, performed in the Post-graduation Program in Education, of the Universidade Federal de São Carlos UFSCar in the "Teaching Methodology" area, in the "Teaching and Learning Process in different contexts" research line, being integrant part of the investigative jobs that have been performed by the Writing and Reading Acquisition: teaching and learning process research Group. In the second semester of 2007, it was offered to the teachers of different schools - public and private - in the city of São Carlos a course of extension named Literacy: Reflections on the knowledge in the first year of the Fundamental Teaching - PROEX/UFSCar, having as one of the goals argue about evaluative processes for the first year of the Fundamental Teaching, with duration of nine years. Thus, we seek to investigate how to configure descriptors and criteria set that form some evaluative instruments collectively built, for the native language acquisition process comprehension. Going through the "Collaborative Methodology" presuppose, the main goal of this research centered in elaborate evaluative instruments , starting from a work collaborative among teachers, research partners, and researchers, boarding the conceptions on evaluation of the participants, the characteristics that they attributed to the evaluative instruments and the implications that such instruments would bring to the educational intervention process . The discussions in studies group and the speeches recordings transcriptions were used as procedures for data collection. The studies on evaluation and some School concepts of Vigotski carried us to reflect about the transformations possibilities in the teaching and learning processes concerned to the evaluation and to the learning levels attribution referring to the literacy process. We left of the principle that clearness and systematization lack of the evaluative process turns it somewhat superficial. With this research we verified that we cannot disregard the importance of evaluative instruments systematization, once it can be a mechanism able to signal to the teacher the students needs that, this way, will be able to plan and to guide his intervention work and his teaching activities. This work provided reflexive activities on the configuration and on evaluative activities elaboration that carried us to a better acquisition process comprehension of the reading and of the writing, indispensable for the possible planning of the educational action. Finally, the result of this study served of guide to base the planning and the research action that integrates the project Learning Communities: it bets on learning quality, in the differences equality and in school administration democratization , financed by the FAPESP and by CNPq, inserted in the axis: Reading and Writing learning .
Keywords: Avaliação; Instrumentos de avaliação; Leitura e escrita; Educação - formação; Formação de professores; Evaluative instruments; Evaluation; Reading; Writing; Teacher formation; CIENCIAS HUMANAS::EDUCACAO